2020
DOI: 10.1111/hiv.12935
|View full text |Cite
|
Sign up to set email alerts
|

What do the changing patterns of comorbidity burden in people living with HIV mean for long‐term management? Perspectives from European HIV cohorts

Abstract: Undoubtedly, comorbidities complicate long‐term HIV management and have significant cost implications for healthcare systems. A better understanding of these comorbidities and underlying causes would allow for a more considered and proactive approach to the long‐term management of HIV. This review examines cross‐sectional analyses of six European cohort studies (Athens Multicenter AIDS Cohort Study, Aquitaine Cohort, EuroSIDA Cohort study, French claims EGB, German InGef Cohort and the Italian Cohort of Indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
(43 reference statements)
0
14
0
Order By: Relevance
“…For individuals with access to early diagnosis and robust treatment options, lifespan can be similar to uninfected individuals ( Marcus et al., 2016 , 2020 ; May et al., 2014 ). Unfortunately, chronic HIV and long-term use of ART substantially increase the risk of comorbid diseases ( d'Arminio Monforte et al., 2020 ; Ruzicka et al., 2019 ), meaning the quality of the added lifespan may be worse ( Collins and Armstrong, 2020 ). These comorbidities include cardiovascular ( Freiberg et al., 2013 ; Triant et al., 2007 ), liver ( Perazzo and Luz, 2017 ) and kidney disease ( Naicker et al., 2015 ), cognitive impairment and neuropsychiatric disorders such as depression, substance abuse, and anxiety ( Cook et al., 2018 ; Milanini et al., 2017 ; Rubin and Maki, 2019 ; Saylor et al., 2016 ; Shiau et al., 2017 ), a number of non-AIDS defining cancers, and metabolic diseases such as diabetes ( Hernandez-Romieu et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…For individuals with access to early diagnosis and robust treatment options, lifespan can be similar to uninfected individuals ( Marcus et al., 2016 , 2020 ; May et al., 2014 ). Unfortunately, chronic HIV and long-term use of ART substantially increase the risk of comorbid diseases ( d'Arminio Monforte et al., 2020 ; Ruzicka et al., 2019 ), meaning the quality of the added lifespan may be worse ( Collins and Armstrong, 2020 ). These comorbidities include cardiovascular ( Freiberg et al., 2013 ; Triant et al., 2007 ), liver ( Perazzo and Luz, 2017 ) and kidney disease ( Naicker et al., 2015 ), cognitive impairment and neuropsychiatric disorders such as depression, substance abuse, and anxiety ( Cook et al., 2018 ; Milanini et al., 2017 ; Rubin and Maki, 2019 ; Saylor et al., 2016 ; Shiau et al., 2017 ), a number of non-AIDS defining cancers, and metabolic diseases such as diabetes ( Hernandez-Romieu et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Following the introduction of the first highly effective antiretroviral therapy (ART) regimens in 1996, the widespread use of ART has transformed HIV care [ 1 , 2 ]. ART suppresses viral replication and thus prevents HIV from destroying the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of individual comorbidities and multimorbidity is higher in people with HIV than in their counterparts without HIV, [2][3][4][5] and the impact of this higher prevalence is not fully understood. In this study, we have used the electronic record of a university-based practice caring for a large, diverse population with HIV and demonstrated that: (1) Comorbidities with primarily functional consequences had a prevalence as high as those with a direct impact on mortality; (2) Different comorbidities had different relationships to age and (3) Although age and number of years with an HIV diagnosis were associated with both high-risk and functional comorbidities as a group, being Hispanic, cisgender female and FTM transgender were associated with functional comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of effective anti-retroviral medication, people are living with HIV as a chronic disease. Although many people with HIV can live to near-normal life spans, 1 they are at higher risk than their HIV negative counterparts for comorbidities [2][3][4][5] like heart disease, 6 bone disease 7 and neuropsychiatric illnesses like depression, 8 as well as geriatric syndromes like falls and frailty. 9 Geriatric assessment, which evaluates the impact of medical and psychosocial factors on individual's function, has been proposed as a way to help optimise care of people with HIV as they age.…”
Section: Introductionmentioning
confidence: 99%